The Influence of Trust, Perceived Ease, and Promotion on the Decision to Use the SPayLater Payment Method in Surabaya - Safi’i, Denisa Putriramadhani; Supriyono (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The significant increase in internet penetration in Indonesia has driven the development of information technology by connecting more individuals to the digital world, which ultimately affects various sectors, including the financial sector, as evidenced by the emergence of technology-based financial institutions that are beginning to dominate transactions, namely financial technology (fintech). BNPL, or what is more commonly known as paylater, has now become an attractive payment option for people with limited budgets. This study aims to identify and analyze the influence of trust, perceived ease, and promotion on the decision to use the SPayLater payment method in Surabaya. This research is a quantitative study with data collected through questionnaires. The analysis technique used in this study is SEM with a component-based approach using PLS as the analysis tool. The results from 98 respondents indicate that trust, perceived ease, and promotion have a positive and significant effect on usage decisions, with the highest factor loading value found in the indicator of engaging content creation under the promotion variable, and the strongest influence given by the perceived ease variable.